Method for extracting and separating trace copper and cobalt in ultra-low vanadium titano-magnetite flotation sulfur concentrate

By adopting the process flow of roasting-leaching-extraction-hydrolytic precipitation-oxalate conversion in ultra-depleted vanadium titanium magnetite flotation sulfur concentrate, the efficient extraction and separation of trace copper and cobalt is solved, and the acquisition of high-purity products and the effective utilization of resources are achieved.

CN119899940AActive Publication Date: 2025-04-29CENT SOUTH UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510398838.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-04-29
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently extract and separate trace amounts of copper and cobalt in ultra-poor vanadium titanium magnetite flotation sulfur concentrate, especially due to the low grade of copper and cobalt, which leads to low extraction efficiency and difficult product purity to meet high standards.

Method used

The process flow combined with 'roasting-leaching-extraction-hydrolytic precipitation-oxalate conversion' is adopted to promote the calcination process through the calcination additive sodium sulfide, improve the leaching rate of copper and cobalt, and achieve efficient separation and enrichment of copper and cobalt through extraction, hydrolytic precipitation and oxalate conversion.

Benefits of technology

Efficient extraction and separation of trace copper and cobalt in flotation sulfur concentrate was achieved, and crystalline copper sulfate products with purity greater than 99% and cobalt oxalate products with purity greater than 99.99% and cobalt grade greater than 38%, were obtained, improving resource utilization efficiency and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899940A_ABST
    Figure CN119899940A_ABST
Patent Text Reader

Abstract

The invention discloses a method for extracting and separating trace copper and cobalt in ultra-low vanadium titano-magnetite flotation sulfur concentrate, and belongs to the technical field of metallurgy. The method comprises the following steps: mixing ultra-lean vanadium titano-magnetite flotation sulfur concentrate containing trace copper and cobalt with sulphide salt, roasting in an air atmosphere to obtain a roasted material, carrying out acid leaching on the roasted material to obtain a copper-cobalt leaching solution, carrying out selective copper extraction on the copper-cobalt leaching solution to realize copper-cobalt separation to obtain a copper solution and cobalt-containing raffinate, and carrying out evaporative crystallization on the copper solution to obtain a copper salt product, and the cobalt-containing raffinate is subjected to hydrolysis iron removal, cobalt precipitation, acidolysis and oxalate conversion to obtain a cobalt oxalate product. By means of the method, efficient extraction of trace copper and cobalt in the ultra-lean vanadium titano-magnetite flotation sulfur concentrate can be achieved, a crystalline copper sulfate product with the purity larger than 99% and a cobalt oxalate product with the purity larger than 99.99% and the cobalt grade larger than 38% can be obtained, and resource utilization of the ultra-lean vanadium titano-magnetite flotation sulfur concentrate is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for extracting copper and cobalt from sulfur concentrate, in particular to a method for extracting and separating trace copper and cobalt from ultra-poor vanadium-titanium magnetite flotation sulfur concentrate, belonging to the technical field of metallurgy. Background Art

[0002] Copper and cobalt are widely used in aviation, electronics, electricity, machinery manufacturing, automobiles, chemicals, new energy and high-end equipment. The flotation sulfur concentrate of ultra-poor vanadium-titanium magnetite is usually used directly to make sulfuric acid. It contains only trace amounts of valuable elements such as copper and cobalt, and is difficult to extract directly. Existing flotation, pyrometallurgy, and biological technologies are difficult to efficiently recover copper and cobalt from flotation sulfur concentrate, especially the flotation sulfur concentrate of ultra-poor vanadium-titanium magnetite containing only trace amounts of copper and cobalt. For example: flotation technology has high requirements on the properties of the ore, the flotation process is relatively complicated, and it is difficult to obtain ideal separation indicators; pyrometallurgy technology is relatively inefficient, energy-consuming, highly polluting, and has high requirements for equipment and complex processes; biotechnology has a slow leaching rate, strict environmental conditions, and a limited leaching rate. Summary of the invention

[0003] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for extracting and separating trace copper and cobalt in the flotation sulfur concentrate of ultra-poor vanadium-titanium magnetite. The method adopts a process flow combining "roasting-leaching-extraction-hydrolysis precipitation-oxalate conversion", which can not only realize the efficient extraction of trace copper and cobalt resources in the flotation sulfur concentrate, but also obtain a crystalline copper sulfate product with a purity greater than 99% and a cobalt oxalate product with a purity greater than 99.99% and a cobalt grade greater than 38%, thereby realizing the resource utilization of the flotation sulfur concentrate containing ultra-poor vanadium-titanium magnetite.

[0004] In order to achieve the above technical objectives, the present invention provides a method for extracting and separating trace copper and cobalt from ultra-poor vanadium-titanium magnetite flotation sulfur concentrate, which comprises the following steps:

[0005] (1) The ultra-low vanadium-titanium magnetite flotation sulfur concentrate containing trace amounts of copper and cobalt is mixed with a sulfide salt and roasted in an air atmosphere to obtain a roasted material; the mass ratio of the ultra-low vanadium-titanium magnetite flotation sulfur concentrate containing trace amounts of copper and cobalt to the sulfide salt is 100:1-5; the sulfide salt is sodium sulfide;

[0006] (2) acid leaching the calcined material to obtain a copper-cobalt leaching solution;

[0007] (3) The copper-cobalt leaching solution is subjected to selective extraction of copper to achieve separation of copper and cobalt, thereby obtaining a copper solution and a cobalt-containing raffinate;

[0008] (4) the copper solution is evaporated and crystallized to obtain a crystalline copper salt product;

[0009] (5) The cobalt-containing raffinate is subjected to hydrolysis to remove iron, precipitate cobalt and acid hydrolyze to obtain a cobalt solution;

[0010] (6) The cobalt solution is converted into oxalate to obtain a cobalt oxalate product.

[0011] The invention aims at the distribution of copper and cobalt in the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt and the composition characteristics of the minerals. The key lies in using sulfide salt as a roasting aid to perform high-temperature decomposition of the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt under an air atmosphere. In the high-temperature process, the sulfide salt can dissociate sulfur anions, and the sulfur anions can be converted into sulfur dioxide gas, so that the materials are loose and not easy to agglomerate during the roasting process, and the strong reducing property of the sulfur anions can reduce the oxidation degree of metal ions such as cobalt, thereby facilitating the leaching effect of metal elements such as copper and cobalt. At the same time, roasting in an air atmosphere enables the sulfide ore to be fully oxidized and decomposed, which is conducive to the exposure of minerals such as copper and cobalt wrapped in the sulfide ore, and the decomposition of minerals such as copper sulfide and cobalt sulfide, and further improves the leaching effect of minerals containing copper and cobalt. In addition, since the copper and cobalt grades in the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate are very low, the concentrations of copper and cobalt in the copper-cobalt leachate are very low. However, copper and cobalt can be enriched through extraction, stripping and hydrolysis to obtain high-concentration copper solution and cobalt solution, which is beneficial to the subsequent evaporation and crystallization to obtain crystalline copper sulfate products, as well as oxalate conversion to obtain cobalt oxalate products.

[0012] As a preferred solution, the copper and cobalt in the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt mainly exist in the form of copper sulfide and cobalt sulfide minerals, and a small amount exists in copper oxide and cobalt oxide minerals. The total copper grade in the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt is about 0.225%, and the total cobalt grade is about 0.096%, which is difficult to extract directly.

[0013] The mass ratio of the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt of the present invention to the sulfide salt is 100:1~5. If the mass ratio of the sulfide salt is too low, the material will be easily agglomerated, and the cobalt ions will be severely oxidized, which will eventually lead to incomplete leaching of copper and cobalt. As the mass ratio of the sulfide salt increases, it is beneficial to the leaching of copper and cobalt from the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt. However, when the mass ratio of the sulfide salt is too high, it will lead to excessive reduction, which is also unfavorable for the leaching effect of copper and cobalt. Therefore, the mass ratio of the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt to the sulfide salt is further preferably 100:2~4.

[0014] The sulfide salt of the present invention is sodium sulfide. Sodium sulfide can be dissociated into sodium ions and sulfur anions at high temperatures. Sulfur anions are easily oxidized and converted into sulfur dioxide gas, and the discharge makes the material loose, and the oxidation degree of cobalt ions can be controlled to reduce them to divalent cobalt ions that are easier to leach, while sodium ions can replace copper ions and cobalt ions. Of course, other sulfide salts can also achieve similar effects, but other sulfide salts may introduce unfavorable impurity cations, which have an adverse effect on the subsequent purification of copper and cobalt. Therefore, the preferred sulfide salt of the present invention is sodium sulfide. If an auxiliary agent without sulfur anions is used, the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt is easy to agglomerate and cobalt ions are severely oxidized during the high-temperature roasting process under air atmosphere, thereby causing the copper and cobalt element leaching rate in copper sulfide and cobalt sulfide ores to be low.

[0015] As a preferred solution, the roasting conditions are: the roasting temperature is 500~700℃, and the roasting time is 2~4h. If the roasting temperature is too low, the sulfide ore will be incompletely oxidized, and the lattice of the copper sulfide mineral and the cobalt sulfide mineral will not be fully destroyed, thereby affecting the subsequent leaching of copper and cobalt; if the roasting temperature is too high, the iron impurities will form dense ferrites with copper and cobalt, which is not conducive to leaching and the cost is higher. If the roasting time is too short, the sulfide ore will be incompletely oxidized; if the roasting time is too long, the power consumption will increase, and the leaching effect will not be significantly improved. A further preferred roasting temperature is 600~650℃. A further preferred roasting time is 2~3h.

[0016] As a preferred solution, the acid leaching conditions are: sulfuric acid is used as the leaching agent, the solid-liquid ratio is 1g:4mL~1g:6mL, the amount of the leaching agent is 100~300g / L, the stirring speed is 200~400r / min, the leaching temperature is 30~80℃, and the leaching time is 0.5~3.0h. Based on the sulfide salt-assisted roasting of the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt, the preferred acid leaching conditions can ensure that the copper leaching rate reaches 90~100%, and the cobalt leaching rate reaches 85~95%. The amount of leaching agent and the leaching temperature during acid leaching are the main factors affecting the leaching effect. As the leaching temperature increases from room temperature to 50°C, the leaching rates of copper and cobalt remain almost unchanged, but when it continues to increase to 80°C, the leaching rates of copper and cobalt increase by about 10%. The further preferred leaching temperature is 60-80°C, and the more preferred leaching temperature is 70-80°C, with 80°C being the optimal leaching temperature. When the amount of leaching agent increases from 100 g / L to 200 g / L, the leaching rates of copper and cobalt elements increase. When the amount of leaching agent is further increased to 300 g / L, the leaching rates of copper and cobalt elements decrease slightly. Therefore, the further preferred amount of leaching agent is 150-200 g / L. In contrast, the leaching effect is best when the amount of leaching agent is 200 g / L. The solid ratio of the leaching liquid and the leaching time also have a certain influence on the leaching effect. For example, as the solid-liquid ratio increases from 1g:4mL to 1g:5mL, the leaching rates of copper and cobalt increase. When the solid-liquid ratio is further increased to 1g:6mL, the leaching rates of copper and cobalt do not increase significantly. The leaching effect is best when the solid-liquid ratio is 1g:5mL. When the leaching time increases from 0.5h to 1h, the leaching rates of copper and cobalt increase slightly. After the leaching time is further increased to 1.5h, the leaching rates of copper and cobalt do not increase significantly. The leaching time is further preferably 1h~1.5h.

[0017] As a preferred scheme, the process of selective extraction of copper includes extraction and stripping: the extraction conditions are: using Lix984 as the extractant, the volume concentration of Lix984 in the extracted organic phase is 10~20%, the extraction phase ratio is O / A=1:0.5~2, and the extraction time is 3~7min; the stripping conditions are: using sulfuric acid solution as the stripping agent, the stripping phase ratio is A / O=1:0.5~2, and the stripping time is 2~11min.

[0018] In the extraction process, the preferred Lix984 is used as a selective extractant for copper ions, and is used for the extraction and separation of copper ions and cobalt ions in the copper-cobalt leachate. In the extraction process, the effect of O / A on the extraction and separation of copper ions and cobalt ions is more obvious. As the amount of the extracted aqueous phase increases, the extraction effect becomes worse. Therefore, the further preferred extraction ratio is O / A=1:1~1.5, and when O / A=1:1, the extraction rate of copper ions is high, and there are fewer impurities. In addition, as the extraction time increases, the extraction effect first increases and then weakens, so the extraction effect is best at 4~6min, so the optimal extraction time is 5min. The extraction organic phase also contains a diluent, such as sulfonated kerosene.

[0019] In the stripping process, 150-200 g / L sulfuric acid solution is used as the stripping agent, which can efficiently elute the copper ions in the copper-bearing organic phase to obtain a copper sulfate solution with a copper ion concentration of 8-10 g / L. The copper sulfate solution is further evaporated and crystallized at a temperature of 60-80°C to obtain a crystalline copper sulfate product with a purity greater than 99%.

[0020] As a preferred solution, the conditions for removing iron are: adjusting the pH to 3.5-4.0, and the precipitation time is 0.5-2.5 hours at a temperature of 80-85° C. Under the preferred conditions, the preferred hydrolysis and precipitation of iron ion impurities is achieved, which is conducive to obtaining a cobalt solution with higher purity.

[0021] As a preferred solution, the cobalt precipitation conditions are: adjusting the pH to 8.0-8.3, at a temperature of 60-70° C., and the precipitation time is 0.25-1 h. Under the preferred conditions, efficient hydrolysis and precipitation of cobalt ions is achieved, which is beneficial to the enrichment of cobalt elements.

[0022] The concentration of cobalt element in the cobalt solution obtained by the present invention is 2.5-2.7 g / L.

[0023] The cobalt solution of the present invention is converted by adding ammonium oxalate in an amount of 2.5-2.7 g / L, and precipitated to obtain a cobalt oxalate product with a purity greater than 99.99% and a cobalt grade greater than 38%.

[0024] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0025] 1. The present invention improves the acid leaching extraction efficiency of copper and cobalt by performing a special roasting process on the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt. The copper leaching rate can reach up to 95.15%, the cobalt leaching rate can reach up to 86.55%, and the concentrations of copper and cobalt in the leachate can reach 0.846 g / L and 0.261 g / L, respectively. Compared with direct leaching, the leaching rate is greatly improved.

[0026] 2. The present invention adopts extraction separation, evaporation crystallization, hydrolysis precipitation and oxalic acid conversion processes to the acid leaching solution, so as to obtain a copper sulfate solution with a copper concentration of 8-10 g / L and a cobalt-rich solution with a cobalt concentration of 2.5-2.7 g / L. After evaporation crystallization and oxalic acid conversion, a crystalline copper sulfate product with a purity greater than 99% and a cobalt oxalate product with a purity greater than 99.99% and a cobalt grade greater than 38% can be obtained respectively, thereby greatly improving the production efficiency and economic benefits of copper products and cobalt products. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention provides a process flow chart for extracting and separating copper and cobalt from the flotation sulfur concentrate of ultra-poor vanadium-titanium magnetite containing trace amounts of copper and cobalt.

[0028] Figure 2 The XRD spectrum of the flotation sulfur concentrate of the ultra-poor vanadium-titanium magnetite containing trace amounts of copper and cobalt of the present invention. DETAILED DESCRIPTION

[0029] The following specific examples are intended to further illustrate the present invention rather than to limit the scope of protection of the claims.

[0030] The ultra-poor vanadium-titanium magnetite flotation sulfur concentrate raw material used in the following examples is:

[0031] A domestic mining company produces 18,000 tons of ultra-poor vanadium-titanium magnetite flotation sulfur concentrate annually, which contains about 0.225% copper and about 0.096% cobalt. The contents of each component in the sample are shown in Table 1:

[0032]

[0033] XRD pattern Figure 2 As shown, from Figure 2 It can be seen that the characteristic peaks of copper minerals and cobalt minerals are almost invisible, indicating that its grade is extremely low.

[0034] Condition optimization experiment:

[0035] Experimental Group 1:

[0036] Through a series of roasting experiments, the effects of roasting temperature (500~700℃), roasting time (2~4h), type of roasting aids, and dosage of roasting aids on the roasting pretreatment of ultra-poor vanadium-titanium magnetite flotation sulfur concentrate were explored.

[0037] The specific operation process is as follows: weigh 50g of ore sample (-43μm) and 10% of roasting aid into a porcelain boat, and put it into a muffle furnace. The roasting atmosphere is air. According to the muffle furnace rising 10℃ every 1min, set the corresponding temperature and time. After the roasting is completed, cool it to room temperature and weigh it.

[0038] Effect of roasting temperature (500~700℃) on leaching rate: Other experimental conditions were controlled as follows: 50g ore sample, 3h roasting time, air atmosphere, no roasting aid. Direct leaching conditions were: temperature 80℃, stirring speed 300r / min, sulfuric acid concentration 200g / L, solid-liquid ratio 1:5 g / mL, and leaching time 1.5h. The higher the temperature, the higher the leaching rate. When the temperature was raised to 650℃, the leaching rate did not increase significantly when the temperature was further raised. Finally, 650℃ was determined to be the optimal experimental condition.

[0039]

[0040] Effect of roasting time (2~4h) on leaching rate: Other experimental conditions were controlled as follows: 50g ore sample, roasting temperature 650℃, roasting atmosphere air, no roasting aid. Direct leaching conditions were: temperature 80℃, stirring speed 300r / min, sulfuric acid concentration 200g / L, solid-liquid ratio 1:5 g / mL and leaching time 1.5h. The longer the time, the higher the leaching rate. Further increasing the time did not significantly increase the leaching rate. Finally, 3h was determined to be the optimal experimental condition.

[0041]

[0042] Effect of roasting aid type on leaching rate: Other experimental conditions were controlled as follows: ore sample 50g, roasting temperature 650℃, roasting atmosphere air, roasting time 3h, roasting aid dosage 3%. Direct leaching conditions were: temperature 80℃, stirring speed 300r / min, sulfuric acid concentration 200g / L, solid-liquid ratio 1:5 g / mL and leaching time 1.5h. Finally, it was determined that the roasting aid was sodium sulfide as the optimal experimental condition.

[0043]

[0044] Effect of the amount of roasting aid on the leaching rate: Other experimental conditions were controlled as follows: 50g of ore sample, roasting temperature of 650℃, roasting atmosphere of air, roasting time of 3h, and roasting aid of sodium sulfide. Direct leaching conditions were: temperature of 80℃, stirring speed of 300r / min, sulfuric acid concentration of 200g / L, solid-liquid ratio of 1:5 g / mL, and leaching time of 1.5h. Finally, the amount of roasting aid of 3% was determined to be the optimal experimental condition.

[0045]

[0046] The roasting test study found that the optimal roasting conditions are: roasting temperature 650℃, roasting time 3h, roasting aid is sodium sulfide, the amount of roasting aid added is 3%, and roasting is carried out under the conditions of 1 roasting stage.

[0047] Experimental Group 2:

[0048] A series of direct leaching experiments were conducted on the roasted samples to investigate the effects of solid-liquid ratio (1g:4mL~1g:6mL), leaching agent dosage (0~300g / L), stirring speed (200~400r / min), leaching temperature (60~80℃), and leaching time (0.5~3h) on the leaching in sulfur concentrate.

[0049] Effect of stirring speed (200~400r / min) on leaching rate:

[0050] Other experimental conditions were controlled as follows: sulfuric acid concentration 200g / L, leaching temperature 80℃, solid-liquid ratio 1:5 g / mL, leaching time 1.5h. The effect of stirring speed on leaching rate was not obvious. The leaching of copper and cobalt did not change much with the increase of stirring speed. The optimal speed condition was determined to be 300r / min.

[0051]

[0052] Effect of temperature (30~80℃) on leaching rate:

[0053] Other experimental conditions were controlled as follows: stirring speed 300r / min, sulfuric acid concentration 200g / L, solid-liquid ratio 1:5 g / mL, leaching time 1.5h. Temperature has a certain effect on the leaching of copper and cobalt elements. When the temperature increases from room temperature to 50°C, the leaching rate remains almost unchanged. However, when it continues to increase to 80°C, the leaching rates of copper and cobalt elements increase by approximately 20% and 30%, respectively. Therefore, 80°C is determined to be the optimal leaching temperature.

[0054]

[0055] Effect of leaching agent (sulfuric acid) concentration (0~300g / L) on leaching rate:

[0056] Other experimental conditions were controlled as follows: stirring speed 300r / min, temperature 80℃, solid-liquid ratio 1:4 g / mL, leaching time 1h. When the amount of leaching agent increased from 100g / L to 200g / L, the leaching rates of copper and cobalt elements increased. When the amount of leaching agent increased to 300g / L, the leaching rates of copper and cobalt elements decreased slightly. In contrast, the leaching effect was best when the amount of leaching agent was 200g / L. Therefore, 200g / L was determined to be the optimal amount of leaching agent.

[0057]

[0058] Effect of solid-liquid ratio (1:4 g / mL ~1:6 g / mL) on leaching rate:

[0059] Other experimental conditions were controlled as follows: stirring speed 300r / min, temperature 80℃, sulfuric acid concentration 200g / L, leaching time 1.5h. When the solid-liquid ratio increased from 1:4 g / mL to 1:5 g / mL, the leaching rates of copper and cobalt increased. When the solid-liquid ratio increased to 1:6 g / mL, the leaching rates of copper and cobalt did not increase significantly. In contrast, the leaching effect of the solid-liquid ratio of 1:5 g / mL was the best, so 1:5g / mL was determined to be the optimal solid-liquid ratio:

[0060]

[0061] Effect of leaching time (0.5~3.0h) on leaching rate:

[0062] Other experimental conditions were controlled as follows: stirring speed 300r / min, temperature 80℃, sulfuric acid concentration 200g / L, solid-liquid ratio 1:5g / mL. When the leaching time increased from 0.5h to 1.5h, the leaching rates of copper and cobalt increased slightly. After the leaching time increased to 1.5h, the leaching rates of copper and cobalt did not increase significantly, so the leaching time was determined to be 1.5h.

[0063]

[0064] The optimal conditions for direct leaching were determined as follows: temperature 80 °C, stirring speed 300 r / min, particle size -43 μm, sulfuric acid concentration 200 g / L, solid-liquid ratio 1:5 g / mL and leaching time 1.5 h.

[0065] The following examples were carried out under the best conditions obtained from the above optimization experiments:

[0066] Example 1

[0067] This embodiment provides a method for extracting and separating trace copper and cobalt from ultra-depleted vanadium-titanium magnetite flotation sulfur concentrate, comprising the following steps:

[0068] Oxidation roasting: roasting is carried out under the conditions of roasting temperature of 650°C, roasting atmosphere of air, roasting time of 3h, and 3% sodium sulfide (relative to the amount of ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt). The ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace copper and cobalt contains about 0.225% copper and about 0.096% cobalt.

[0069] Leaching: Leaching for 1.5h at a temperature of 80℃, a stirring speed of 300r / min, a sulfuric acid concentration of 200g / L, and a solid-liquid ratio of 1g:5mL. The copper leaching rate is 95.15% and the cobalt leaching rate is 86.55%.

[0070] Extraction of copper: 15% of Lix984 extractant, 85% of sulfonated kerosene as diluent, O / A=1:1, time 5min. The extraction rate was 99.59%.

[0071] Stripping of copper: using 180 g / L sulfuric acid solution, A / O = 1:1, reaction time 5 min, stripping rate 99.91%, copper concentration in the obtained copper sulfate solution was 9.3 g / L.

[0072] Evaporation crystallization: Place the copper sulfate solution on a magnetic stirrer and stir it thoroughly at a stirring speed of 200r / min. The temperature is controlled at 80°C and the reaction time is 5h to obtain a crystalline copper sulfate product with a purity greater than 99%.

[0073] Iron removal: adjust pH to 3.8, at 85℃, reaction time 2h. Iron removal rate is 99.86%, cobalt loss rate is 1.84%.

[0074] Cobalt precipitation: adjust pH to 8.1, at 65°C, reaction time 0.5h. Cobalt precipitation rate is 99.58%.

[0075] Acid dissolution: Use sulfuric acid solution with a pH of 0.5 and a temperature of 65°C to fully dissolve the cobalt enrichment. The concentration of the obtained cobalt solution is 2.57 g / L.

[0076] Precipitation: Mix the cobalt solution with an ammonium oxalate solution of pH=4.8, place the mixture on a magnetic stirrer, stir at 45°C, stir at a stirring speed of 200r / min, and react for 2h to obtain cobalt oxalate precipitation. During the precipitation process, 14~15g / L ammonium oxalate solution is used for every 100mL of cobalt solution, and a cobalt oxalate product with a purity greater than 99.99% and a cobalt grade greater than 38% is obtained by precipitation.

[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for extracting and separating trace copper and cobalt from ultra-poor vanadium-titanium magnetite flotation sulfur concentrate, characterized by: The following steps are involved: (1) The ultra-low vanadium-titanium magnetite flotation sulfur concentrate containing trace amounts of copper and cobalt is mixed with a sulfide salt and roasted in an air atmosphere to obtain a roasted material; the mass ratio of the ultra-low vanadium-titanium magnetite flotation sulfur concentrate containing trace amounts of copper and cobalt to the sulfide salt is 100:1-5; the sulfide salt is sodium sulfide; (2) acid leaching the calcined material to obtain a copper-cobalt leaching solution; (3) The copper-cobalt leaching solution is subjected to selective extraction of copper to achieve separation of copper and cobalt, thereby obtaining a copper solution and a cobalt-containing raffinate; (4) the copper solution is evaporated and crystallized to obtain a crystalline copper salt product; (5) The cobalt-containing raffinate is subjected to hydrolysis to remove iron, precipitate cobalt and acid hydrolyze to obtain a cobalt solution; (6) The cobalt solution is converted into oxalate to obtain a cobalt oxalate product.

2. The method for extracting and separating trace copper and cobalt from the flotation sulfur concentrate of ultra-poor vanadium-titanium magnetite according to claim 1, characterized in that: The copper and cobalt in the ultra-poor vanadium-titanium magnetite flotation sulfur concentrate containing trace amounts of copper and cobalt mainly exist in the form of copper sulfide minerals and cobalt sulfide minerals, and a small amount exists in copper oxide minerals and cobalt oxide minerals.

3. The method for extracting and separating trace copper and cobalt from the flotation sulfur concentrate of ultra-poor vanadium-titanium magnetite according to claim 1 or 2, characterized in that: The calcination conditions are as follows: the calcination temperature is 500-700° C. and the calcination time is 2-4 hours.

4. The method for extracting and separating trace copper and cobalt from the flotation sulfur concentrate of ultra-poor vanadium-titanium magnetite according to claim 1, characterized in that: The acid leaching conditions are: sulfuric acid is used as the leaching agent, the solid-liquid ratio is 1g:4mL~1g:6mL, the amount of the leaching agent is 100~300g / L, the stirring speed is 200~400r / min, the leaching temperature is 30~80℃, and the leaching time is 0.5~3.0h.

5. The method for extracting and separating trace copper and cobalt from the flotation sulfur concentrate of ultra-poor vanadium-titanium magnetite according to claim 1, characterized in that: The process of selectively extracting copper includes extraction and stripping: The extraction conditions are as follows: using Lix984 as the extractant, the volume concentration of Lix984 in the extracted organic phase is 10-20%, the extraction phase ratio is O / A=1:0.5-2, and the extraction time is 3-7 min; The stripping conditions are: using sulfuric acid solution as the stripping agent, the stripping phase ratio is A / O=1:0.5~2, and the stripping time is 2~11min.

6. The method for extracting and separating trace copper and cobalt from the flotation sulfur concentrate of ultra-poor vanadium-titanium magnetite according to claim 1, characterized in that: The conditions for iron removal are: adjusting the pH to 3.5-4.0, at a temperature of 80-85° C., and a precipitation time of 0.5-2.5 h.

7. The method for extracting and separating trace copper and cobalt from the flotation sulfur concentrate of ultra-poor vanadium-titanium magnetite according to claim 1, characterized in that: The cobalt precipitation conditions are as follows: adjusting the pH to 8.0-8.3, at a temperature of 60-70° C., and the precipitation time is 0.25-1 h.

Citation Information

Patent Citations

  • Desulfurizing method for direct reduction of V-Ti magnetite

    CN101020959A

  • Method for separating and preparing high loose ratio and high purity cobalt oxalate from asbolite

    CN101792855A

  • Method for extracting cobalt from vanadic titanomagnetite and preparing superfine cobalt powder

    CN102321797A

  • Method for extraction of valuable components in vanadium-titanium magnetite through oxygen-rich selective leaching

    CN108149015A

  • Method for recovering scandium in ultra-low vanadium titano-magnetite iron separation tailings

    CN117385207A